Characteristics and outcomes of low birth weight infants in Bali - Putu Junara Putra (Indonesian Pediatric Society, 2012)
Background The prevalence and the mortality of low birthweight infants are still high. Low birth weight (LBW) births areresponsible for newborn death. LBW infants are easier to sufferserious health problems and death. Lower infant body weightand younger gestational age are determinants of greater risk ofmortality.Objective To determine the characteristics of LBW infants andtheir outcomes in Sanglah Hospital, Denpasar.Methods This prospective study was conducted on all LBWinfants in the nursery from their time of admission until dischargefor the year of 20 11..Results There were 120 LBW infants admitted to SanglahHospital fromJanuary 2011 to December 2011. The prevalenceofLBW was 8.9%. The birth weight group of 1500ô€°2499 gramshad the highest number of infants (79.2%). The gestational agegroup of 33ô€°36 weeks had 53.3% of the infants, while 68.3% ofthe LBW infants were of the appropriate gestational age. Themost common method of delivery was normal spontaneousdelivery (70%). Moderate asphyxia was observed in 25% of thesubjects, while severe asphyxia was observed in 22.5% of subjects.The mortality rate was 24.2%.Conclusions The prevalence of LBW of all newborns in ourhospital was 8.9%. Severe asphyxia was observed in 22.5% ofsubjects. The mortality rate of the LBW infants was 24.2%. OurLBW infants were most cormnonly in the categories of birth weightof 1500ô€°2499 grams, gestational age was between 33ô€°36 weeks,appropriate for gestational age, as well as delivered spontaneously.[Paediatr lndanes. 2012,52:30003].